INTENSITAS TEBANG BAYANG OPTIMUM DALAM PEMELIHARAAN JALAN HUTAN - Dulsalam Dulsalam; Rahardjo S Suparto (Jurnal Penelitian Hasil Hutan, 1987)
Forest roads requires lots of sun and air to keep them dry. These can be obtained by  "shade felling"  of the stand at both sides OJ the road. The problem in this matter is the question  about  the proper felling  intensity  to render adequate sunshine  and air without  undue  overcutting.Logging companies  tend to fell  as many  trees as possible  to ensure enough  opening  to let sunshine  and air in.A  Least  Significant  Difference  (LSD)  test on the data  obtained from the observation  indicate  that felling  intensity  over 50%  does not provide  better result than 31-41%. It is therefore suggested that shade felling intensity  be kepi at 40%  or less to save time,  man power, cost and forest  resource.